Farm-Raised Channel Catfish - Frank A. Chapman (EDIS)
This document is about Channel catfish (Ictalurus punctatus). Channel catfish belong to the family Ictaluridae, in the large catfish order Siluriformes. The order includes over two thousand species, and most of them inhabit the fresh waters of the tropics. In the United States, the family Ictaluridae is native to the water drainages east of the Rocky Mountains, and contains about forty-three recognized species. Other important commercial species in the family include the blue catfish (I. furcatus), white catfish I. catus), yellow bullhead (I. natalis), brown bullhead (I. nebulosus), black bullhead (I.melas), and the flathead catfish (Pylodictis olivaris). First published in July, 1992.